The Baltic Sea Ecosystem Regulation Mechanism - Hänninen Jari (Crimson Publishers LLC, 2022)
Short communication: Understanding the functioning of the Baltic Sea ecosystem has been one of the most important tasks of the Seili Research Station of the University of Turku, Finland. Understanding requires not only the study of the regulatory mechanisms of the Baltic Sea ecosystem, but also the study of the climatic conditions of the Atlantic, as the climatic conditions of the ocean ultimately determine how the Baltic Sea ecosystem develops.